Organizational Culture on Online Donation Willingness: Mediating Role of Donation Attitude in SNS Contexts - Chen, Chen; Zhang, Zhiqian; Ahn, Jongchang (Journal of Cultural Analysis and Social Change, 2026)
This study aims to examine the factors influencing donation attitudes and willingness to donate via social networking services (SNSs), with a particular focus on exploring the mediating effects of donation attitudes and social network functions. A questionnaire survey was conducted among 357 Chinese social network users. Structural equation modeling (SEM) was employed to analyze the path relationships between variables and further test the mediating effects. The results indicate that Internet technology features and organizational culture not only exert a significant positive impact on donation attitudes but also indirectly influence the public’s desire to donate via SNS through their impact on donation attitudes (mediating effects). Unexpectedly, charitable organizations exert an adverse effect on the public’s willingness to donate using SNS. Although SNS functions can enhance donation attitudes, their mediating impact on willingness is not significant. The findings enrich research perspectives on digital philanthropy by highlighting the roles of Internet technology features, organizational culture, charitable organizations, and social network functions in influencing online donation behaviors. The study provides suggestions for enhancing trust mechanisms, strengthening technical support, and promoting cultural considerations of online fundraising platforms. The sample sources for conducting the questionnaire are all from China, lacking an international comparison.